Penyuluhan Isra’ dan Mi’raj sebagai Upaya Menumbuhkan Kecintaan kepada Rasulullah SAW kepada Anak - Rizal Furqan Ramadhan (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
Isra' Mi'raj Extension Activities are activities in the form of socialization or lectures, often found in the community. This community service activity was carried out at SDN 1 Pucanganak with participants, including students from grades 1 to grade 6, along with teachers and elementary school employees. This community service method consists of three parts, including the observation stage, the implementation stage and the evaluation stage. The observation stage is the stage of visiting and observing the location of the purpose of community service. In addition, at the observation stage, a consultation was carried out with the relevant principals and teachers regarding the decreasing number of elementary-age children idolizing the Prophet Muhammad. The step after observation is implementation. The implementation stage is the core stage in extension activities. The activity was carried out at SDN 1 Pucanganak with 85 students from grade 1 to grade 6 SD. The final step is evaluation. Evaluation is carried out through feedback between presenters and participants or students. The feedback given to the participants came from the material presented by the resource person. Feedback aims to test the level of understanding of the extension participants. From the counselling regarding Isra' Mi'raj, it is hoped that it can increase the love of all students for Rasulullah SWA as well as develop character according to the background and struggle of Rasulullah SAW.